Light-by-light scattering in ultraperipheral heavy-ion collisions at low diphoton masses - Kłusek-Gawenda, Mariola; McNulty, Ronan; Schicker, Rainer; Szczurek, Antoni (Physical review, 2019)
We present a study of photon-photon scattering in the mass range Wγγ<5 GeV. We extend earlier calculations of this cross section for Wγγ>5 GeV into the low mass range where photoproduction of the pseudoscalar resonances η, η′(958) contributes to two-photon final states. We present the elementary photon-photon cross section as a function of diphoton mass Mγγ arising from lepton and quark loop diagrams, and the visible cross section obtained with the gamma-gamma decay branching fractions of the resonances η, η′(958), ηc(1S), ηc(2S), χc0(1P). We derive the corresponding cross sections in ultraperipheral Pb-Pb collisions at √sNN=5.02 TeV by folding the elementary cross section with the heavy-ion photon fluxes. We consider the dominating background of the two photon final state which arises from gamma decays of photoproduced π0-pairs. Such π0-pairs contribute to the background when only two of the four decay photons are within the experimental acceptance, while the other two photons escape undetected. We reduce this background by applying cuts on asymmetries of transverse momenta of the two photons and indicate how the background can be further suppressed using a multivariate sideband analysis. We present the cross section for the signal and the background at midrapidity |η|<0.9, and in the forward rapidity range 2.0<η<4.5.
Gesehen am 02.10.2019